Performance Evaluation of Low-Cost GPS Time Server Based on NTP - Heri Andrianto; Yohana Susanthi; Denny Suryadi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Time synchronization is required to maintain a precise clock. In this paper, a low-cost GPS NTP server has been realized using inexpensive arduino, GPS receiver, and ethernet shield. The performance of low cost GPS NTP server has been compared with the performance of commercial GPS NTP server (TM1000A). The results showed that both time server has synchronization success rate of 100% with average clock offset -8,69 ms for low cost GPS NTP server and -10,1538 ms for TM1000A.  However, TM1000A have better clock offset deviation area compared with low cost GPS NTP server. TM1000A has a smaller clock offset deviation area, which is between -8 ms to -12 ms while low cost GPS NTP server has larger clock offset deviation area, which is between -20 ms to +10 ms. With production costs of less than 29 USD, we offer cheap GPS NTP servers as an alternative GPS NTP server for time synchronization on computer networks.